A Study of Gender Difference of Using Taboo Words in The Euphoria Series - Dwijayani, Ni Made; Beratha, Ni Luh Sutjiati; Sukarini, Ni Wayan (Humanis; Vol 27 No 3 (2023)DO - 10.24843/JH.2023.v27.i03.p09, 2023)
Taboo word is a forbidden word to use in any situation because it can cause discomfort to others, however taboo word can easily be spotted in everyday conversation. With that phenomenon, the analysis is conducted to investigate the use of taboo words and identify the difference between women and men character with the theory from Jay to categorize type of taboo words and a theory from Coates and Lakoff to examine how men and women speak differently. This study used the Euphoria series as a main source of the study due to the popularity of this series among young generation. The findings reveal that out of 229 collected data, ten different categories of taboo words exist in this series which are cursing (17,03%), followed by profanity (8,73%), blasphemy (0,44%), taboo (3,95%), obscenity (8,73%), slang (10,48%), epithet (21,40%), insult and slur (17,47%), and finally scatology (0,87%) and also the difference between women and men in using taboo words. .